LITERATURE REVIEW: SENSITIVITY AND SPECIFICITY OF VDRL AND RPR AS SCREENING TESTS OF SYPHILIS IN PREGNANT WOMEN - Kadarusman, Tamara Audrey; Thirafi, Sacharissa Zerlina Tsarwah; Bangsa, Niki Kusuma; Widyatama, Rufina Adelia; Nugroho, Lutfi Dewanda; Surya, Prima Ardiansah; Lestari, Pudji (Journal of Community Medicine and Public Health Research, 2021)
Early detection of syphilis, especially during pregnancy, is important to prevent comorbidities for the mother and the baby. This study aims to determine whether VDRL is more sensitive and specific than RPR as a diagnostic screening test for syphilis infection in pregnant women. Literature searches for relevant articles were conducted in PubMed, Cochrane, and Proquest using the keywords "VDRL AND RPR AND pregnancy AND syphilis". From the search results, we found 7 articles in Pubmed, 2.290 articles in Proquest, and no relevant articles were found in Cochrane. Title and abstracts were screened for their conformity with the case and clinical questions that had been made. Selected articles were then critically appraised. The results of the study in selected articles indicated that VDRL and RPR showed a false positives rate of 10.5% and 9.6%, respectively. The sensitivity and specificity of VDRL were 71.6% and 89.5%, and those of RPR were 73.5% and 90.5%. VDRL and RPR have a moderate agreement with the TPHA (kappa = 0.6). From these studies it can be concluded that VDRL is not more sensitive and specific than RPR, implying that RPR is a better diagnostic screening test for syphilis infection in pregnant women than VDRL.